Animating erotica without shame: an autoethnographic creative account - Mitkus, Tomas (Creativity Studies, 2024)
This article explores the experience of shame and guilt that is associated with producing explicit erotic animated content. By employing the reflective practice journaling method, this autoethnographic essay discusses cultural and psychological challenges that need to be overcome by an animator from the Western cultural sphere in order to be able to produce content with sexual overtones. Findings suggest that to create erotic content, it is necessary first to overcome psychological barriers. But even then, the ability to portray animated sexual rapport requires specific animation skills and aesthetical understanding that are difficult to transfer from previous experience. The article concludes with a discussion on how to approach erotic content and what possible challenges the creative team may face in a project with erotic overtones.